Reparación integral en el ordenamiento constitucional y las víctimas de desaparición de personas en el Ecuador, periodo 2020-2021. - González Álvarez, Génesis Milena (2023)
When entering the context of the disappearances of people in Ecuador, a complex conglomerate of problems that address this issue must be included. This particular work must focus on comprehensive reparation for direct and indirect victims. Understanding that this figure is one of the judicial measures that protects them with the purpose of repairing the damage caused by the violation of disappearance. There are international standards that have established various parameters on how to carry out this topic, both in the axis of investigation and attention within the search procedure. Ecuador, for its part, has adopted some strategies that meet the needs of these beings who unfortunately suffer from the loss of their loved one. Its highest legal system, the Constitution of the Republic of Ecuador, has established in its article 78 on comprehensive reparation and has agreed to it in other legislations such as the Comprehensive Organic Criminal Code, Organic Code of the Judiciary and others. However, the victims and especially the relatives, friends and civil society that are immersed in this context have spoken out for the non-compliance with these measures. They speak out about the irresponsibility of the Ecuadorian state in fulfilling this state duty that should protect them. It must be understood that with this breach, different rights enshrined in the same articles must be violated, such as the right to know the truth of the facts, restitution, compensation, rehabilitation, effective judicial protection, right to participation, protection , assistance as a victim of this circumstance, etc. It is worth noting the distinguished Ecuadorian cases that have been a fundamental pillar to reflect the serious situation that the country is going through, such as those of Luis Eduardo Guachalá, Juliana Campoverde, the Restrepo brothers, etc. 5 It is necessary to be aware that behind the disappearance of a person, there is a family, a friend, a society that seeks to compensate this damage without losing hope of ever meeting again with that person who could not be located, looking for an answer to your concerns, seeks to know what procedures the state uses to find your loved one, seeks to participate in the actions and proceedings carried out by the entities in charge of this function. Under this reality, this work has the objective of carrying out a legal and doctrinal analysis on comprehensive reparation for victims of disappearance, in order to evaluate the effectiveness of state agencies to grant it as well as to know what rights and guarantees established in the Magna Carta are violated with their breach. For this, it is necessary to analyze documents, legal bodies, internet pages that express themselves in this regard, in addition to conducting interviews with members of the Asfadec and INREDH organizations, which are associations/foundations that are closely linked to this problem in Ecuador. It is expected to reflect the reality of the disappearance of people in the country, as well as to be able to contribute with a possible solution to this violation. Keywords: Disappearance of people – Comprehensive Reparation – Human Rights – Violation – Victims